Electricity storage and renewables : costs and markets to 2030 (International Renewable Energy Agency, 2017)
Battery electricity storage is a key technology in the world's transition to a sustainable energy system. Battery systems can support a wide range of services needed for the transition, from providing frequency response, reserve capacity, black-start capability and other grid services, to storing power in electric vehicles, upgrading mini-grids and supporting "self-consumption" of rooftop solar power. In the longer-term, batteries could support very high levels of variable renewable electricity, specifically by storing surplus energy and releasing it later, when the sun is not shining or the wind not blowing strongly enough. While pumped-hydro systems still dominate electricity storage (with 96% of installed storage capacity in mid-2017), battery systems for stationary applications have started growing rapidly. Wider deployment and the commercialisation of new battery storage technologies has led to rapid cost reductions, notably for lithium-ion batteries, but also for high-temperature sodium-sulphur ("NAS") and so-called "flow" batteries.
"October 2017"
Keywords: Energy storage.; Electric power production.; Renewable energy sources.; elektronické knihy; electronic books